TEACHER TALK REALIZATION IN THE STAGES OF SCIENTIFIC APPROACH: AN INTERPERSONAL MEANING ANALYSIS OF EFL CLASSROOM DISCOURSE - Ai, Setialis (2018)
Teacher talk is considered an essential part in making language classroom active since it can foster students' involvement in teaching-learning activities. However, English teachers may not realize that their talk or language has the potential to build (or ruin) rapport with their students. In response to the issue, the present research examines the interpersonal meaning of teacher talk in the teachinglearning activities through the stages of scientific approach. Employing a qualitative design, this research explores the speech functions and mood typicality realized in the teacher talk. To achieve these objectives, a sample of EFL teaching-learning interaction which involves one male EFL teacher has been selected purposively. Data were collected by recording and note-taking the teaching-learning activities in four sessions. The data were analyzed by focusing on the speech function and mood typicality realized in the teacher talk. The results show that the speech function mostly realized by the teacher is question, which functions to attract the students' attention, to gain information from the students, and to help the students explore the materials. The teacher also realized his talk in the typical mood choice, implying that he was communicating in accordance with the normal expectation. Thus, the success of communicating the content of the learning is determined by the teacher's interpersonal relationship with the students. It is expected that the description of interpersonal meaning of teacher talk can provide an insights for teachers to use teacher talk which is appropriate to the students' characteristics.;--- Ujaran guru merupakan hal penting yang dapat meningkatkan keaktifan siswa dalam pembelajaran bahasa Inggris di kelas. Namun, para guru bahasa Inggris sering tidak menyadari bahwa ujaran mereka mempengaruhi hubungan interpersonal mereka dengan siswa . Penelitian ini bertujuan untuk menganalisis makna interpersonal ujaran guru dalam kegiatan belajar-mengajar yang menggunakan pendekatan saintifik. Dengan menggunakan desain kualitatif, penelitian ini membahas speech function dan mood typicality yang direalisasikan dalam ujaran guru. Responden dalam penelitian ini yaitu satu orang guru mata pelajaran Bahasa Inggris laki-laki yang dipilih secara purposive. Data dikumpulkan dengan merekam kegiatan belajar-mengajar sebanyak empat pertemuan and mencatat hal-hal penting yang terjadi selama kegiatan pembelajaran berlangsung. Data tersebut kemudian dianalisis dengan fokus pada pembahasan speech function dan mood typicality yang direalisasikan dalam ujaran guru. Hasil penelitian menunjukkan bahwa speech function yang paling sering direalisasikan guru melalui ujarannya yaitu question, yang berfungsi untuk menarik perhatian siswa, memperoleh informasi dari siswa, dan membantu siswa untuk mengeksplorasi materi pembelajaran. Selain itu, guru tersebut juga merealisasikan ujarannya dalam bentuk typical mood choice, yang mengindikasikan dia berkomunikasi dengan siswa di kelas melalui cara yang normal. Dapat disimpulkan bahwa keberhasilan guru dalam mengkomunikasikan konten tidak terlepas dari hubungan interpersonalnya dengan siswa. Pembahasan mengenai makna interpersonal ujaran guru ini diharapkan dapat memberikan pemahaman lebih bagi para guru untuk menggunakan ujaran di kelas yang sesuai dengan karakter siswa.